The long-waited high level evidence in thoracic surgery - Tu, Cheng-Che; Hsu, Po-Kuei (Annals of Translational Medicine, 2016)
Bendixen and colleagues conducted this well-constructed randomized trial in patients who underwent curative surgery for stage I non-small cell lung cancer, comparing the postoperative pain and quality of life (QoL) after anterolateral thoracotomy to video-assisted thoracoscopic surgery (VATS) (1). Being one of the most lethal cancer, the incidence of lung cancer is increasing around the world (2). With the advent of low dose chest computed tomography (CT) scan, more and more indeterminate lung nodules and early stage lung cancers have been diagnosed, and many of them would eventually receive surgical resections (3), inasmuch as this trend, a proper suggestion on type of operation becomes paramount. Although it is reasonable to assume that VATS is superior to thoracotomy in terms of postoperative wound pain based on the literature, most of these evidences are non-randomized comparative studies (4,5). Before this study, the debates between these two procedures have never been settled. Revealed by this trial, superior outcome in both postoperative pain and QoL are seen in VATS group. However, a further investigation comparing VATS to “posterolateral thoracotomy” or comparison between VATS with different number of port is still needed.